AKTIVITAS RE-EKSPOR OLEH IMPORTIR KOPI DUNIA DAN IMPLIKASINYA BAGI INDONESIA (World Coffee Re-Export Activities and the Implications for Indonesia) - MUHAMMAD IBNU; FIRDASARI FIRDASARI (Universitas Mulawarman (University of Mulawarman), 2023)
Coffee is the most traded plantation commodity in the world. The data shows that currently there are more countries trading coffee than those producing it. In other words, many countries import coffee and then re-export it, such as France, Germany and the United States. This study aims to answer questions (1) How does the map of Indonesian coffee export destinations compare to the importing countries that carry out re-exports? (2) How is the quantity (volume) and value of Indonesian coffee exports compared to the importing countries that carry out re-exports? To answer these questions, this research utilizes secondary data for the last five years (2017-2021) from FAO (FAOSTAT). The data were processed quantitatively using the Microsoft Excel version 2021. The results showed that France, Germany and America have more export destinations than Indonesia. The re-exporting countries also seem to have started to outperform Indonesia in the coffee trade, both in quantity and value. Therefore, it is important for national coffee stakeholders to think about the sustainability of Indonesian coffee production and trade by creating various innovations that increase added value and seek new market opportunities.